AUTHORIAL AND NON-AUTHORIAL AFFECT AND ITS RELATION TO SPEAKER’S INTENTION (AN APPRAISALS THEORY APPROACH) - Dwi Meisyitah Ananda; Mangatur Rudolf Nababan; Riyadi Santosa (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2019)
Recent studies on appraisals signifies the continuous development to delve further on appraisals theory. Like previous studies, this study focuses on one of aspects in appraisals called affect. The main concern is to study the authorial and non-authorial, authorial-non authorial affect in speech. The aims are to find out the types of affect used and its relation with speakers’ intentionand also the graduation shift that occurs in its Indonesian translation. This study used descriptive qualitative approach. The data were obtained through content analysis and were analyzed by using domain, taxonomy, and componential analysis. The result of this study shows that the amount of authorial-non authorial affect is higher than the amount of authorial and non-authorial affect. In relation to translation study, it is also found that there are 10 graduation shifts that occur in in the target text caused by translation techniques. The study implicates that the speeches mainly used authorial-non authorial affect to shows that the speakers and audience are on the same page on certain issues and the graduation shifts in target text change the affect perceived by the target readers.